Tax Compliance as a Governance Outcome: Systematic Evidence on ESG Integration in Corporate Fiscal Behavior - Lane, Penny; Kurniawati, Heny (Institut Bisnis dan Informatika Kesatuan, 2026)
Global scrutiny pressures firms toward responsible tax and sustainability. This study investigates the role of ESG practices on corporate tax compliance behavior. This study employs a qualitative approach using a systematic literature review of 30 Scopus-indexed articles published between 2021 and 2025. The findings reveal a mixed pattern, most evidence suggests that strong ESG performance and disclosure reduce tax avoidance and foster transparency, although variations emerge across ESG dimensions, governance mechanisms, and institutional environments. Key enabling determinants include disclosure specificity (adherence to GRI tax standards), board oversight strength, well-aligned fiscal-environmental incentive structures, ethical organizational culture, and robust internal control systems. Conversely, the impact of ESG on tax compliance weakens due to heterogeneous ESG and tax measurement proxies, a lack of reporting standard integration, and inconsistencies in legal enforcement across jurisdictions. The gap analysis highlights the urgent need for standardization of corporate tax responsibility indicators, the application of virtue-ethics governance models in emerging markets, and more rigorous causal testing using IV or DID approaches to address simultaneity and endogeneity. This study contributes to advancing sustainability-driven fiscal governance frameworks and offers actionable insights for corporations aiming to integrate ESG commitments into accountable tax governance.